Web Seminar From Zero to Hero Marketing Sosial Media - Baiq Dinna Widiyasti; Zahrah Zahrah; Rini Anggriani; Lady Faerrosa; Rizky Raharjo (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The rise of social media users is a positive opportunity for business/SME owners to take advantage of these communication facilities as a means of introducing their products. Social media is a place where consumers are more receptive to product messages. Consumers are more receptive to marketing messages on social media because social media makes it possible to interact more and market brands from different angles. Students of Bumigora University and Saraswati University are also expected to have the opportunity to have a business, so that the mindset of students is not only graduating from campus to find work but also to create jobs, starting with entrepreneurship. The role of social media as a piece of marketing advice is to give a better marketing performance. Web seminars are held to provide development for students and provide a forum for students to increase their knowledge and skills in utilizing social marketing media. Some students are already doing marketing with social media to get started, but with the existing issues and current conditions, of course, there will be many questions that need to be supported so that they can maximize the use of social media as a marketing platform